1968
DOI: 10.1175/1520-0493(1968)096<0365:roatmc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

ROLE OF A TROPICAL “MARITIME CONTINENT” IN THE ATMOSPHERIC CIRCULATION1

Abstract: Thunderstorm frequency and amount of moisture above 500 mb. both indicate that the equatorial regions of South America and Africa and the "maritime continent" of Indonesia and the Carolines generate a much greater amount of heat for export than do equatorial oceanic regions. Over the maritime continent in January 1963, heat generated from excessive rains was efficiently transported northward and through conversion of potential to kinetic energy probably helped maintain an intense subtropical jet stream. In Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
246
0
6

Year Published

1981
1981
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(257 citation statements)
references
References 14 publications
5
246
0
6
Order By: Relevance
“…The unique location of the tropical Maritime Continent (MC) (Ramage 1968) cause complex patterns of weather and climate variability over different timescales. Seasonal precipitation variability is affected mainly by the Asian and Australian Monsoon and the position of the Intertropical Convergence Zone (Hamada et al 2002;Aldrian and Susanto 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The unique location of the tropical Maritime Continent (MC) (Ramage 1968) cause complex patterns of weather and climate variability over different timescales. Seasonal precipitation variability is affected mainly by the Asian and Australian Monsoon and the position of the Intertropical Convergence Zone (Hamada et al 2002;Aldrian and Susanto 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a series of research work on the interannual fluctuations of the tropical winter monsoon was conducted. Ramage (1968) analyzed the winter monsoon circulation and associated precipitation during January 1963 and January 1964. He suggested that a strong easterly wind at the 200mb level near Singapore was associated with the strong winter monsoon at the low level.…”
Section: Introductionmentioning
confidence: 99%
“…The tropical Indo-Pacific domain is one of the key regions controlling the global climate variability (Ramage 1968;Neelin et al 1998;Torrence and Webster 1998;Lau et al 2000Lau et al , 2002Wang et al 2000;Wang and Zhang 2002;Kosaka and Xie 2013). The large-scale atmospheric circulation over this region plays an important role in not only influencing the variability of the tropical climate systems but also transferring their impacts remotely through teleconnections (Wang and Zhang 2002;Cai et al 2011;Sun and Zhou 2013).…”
Section: Introductionmentioning
confidence: 99%